EFFECT OF CALCUSOLTM ON CuZnSOD EXPRESSION IN MICE RENAL OF NEPHROLITHIASIS MODEL - Arief Azhary; Sri Widyarti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
This study aimed to determine the effect of traditional medicine, CalcusolTM, on number of cells expressing CuZnSOD in mice renal of nephrolithiasis model. Eight weeks old Swiss strain male mice (Mus musculus) were divided into five groups: (A) control, (B) nephrolithiasis, (C) CalcusolTM, (D) nephrolithiasis & CalcusolTM, and (E) nephrolithiasis & CalcusolTM simultaneously. Nephrolithiasis was induced by applying porang tuber (Amor- phophallus muelleri) flour 0.06 mg/g of body weight during 3 months. CalcusolTM is traditional medicine, made of tempuyung leaves extract with Saccharum lactis as additional substance. The dosage for CalcusolTM treatment was 3.3 mg/g of body weight. After 3 months treatment, the mice were killed by neck-dislocation, the kidneys were isolated and prepared for paraffin histology. CuZnSOD was analyzed by immunohistochemistry (IHC), using rabbit policlonal antibody anti-SOD1 (Bioss, bs-1079R) as primary antibody. Tissues were observed under Olympus BX51, 400x mag- nification. Images were documented with Olympus Digital Camera DP20. The histology images were analized in Immunoratio software online (URL: http://153.1.200.58:8080/immunoratio/) to receive the percentage of number of cells expressing CuZnSOD. The result showed that CalcusolTM administration could decrease number of cells expressing CuZnSOD in kidney significantly (P<0.05). It was supposed that antioxidant content in CalcusolTM could scavenge ROS directly with no induction of CuZnSOD production in cell.